Experiência de Deus e educação escolar: a dimensão transcendental da pessoa humana no encontro com o estético e o lúdico - Zonta, José Ricardo (2009)
The research which is now presented, establishes a convergence relation between the experience of God and school education. It shows how the school can deal with such issue with no religious proselytism. The extreme aim of education is humanization and all the authentic experience of God humanizes, then, in this point, the educational process as well as the religious experience is. The transcendental being wishes a meaning which guides his knowledge, needs answers, searches and only rests when he can rest in a Meaning that to everything can give a meaning that it is granted by the extreme issues. And a fundamental role is a duty of education: not allow the human beings absolutize what has no sense, what does not humanize. But what is education based on that it can favor the Meaning that it humanizes? But how would this Meaning with Absolute essence present itself? In this perspective we propose a grounded and creative pedagogy of admiration, which structures itself on the life experience principles and strategies from the Playful and the Esthetic when proving the possibility of a political-educational project where Beauty and Joy appear as the face of Meaning, and why not saying as the God s face that humanizes. By the pedagogy proposed here, the Meaning of life forms to the Beauty and Joy, which leads us to build our human identity by the Good and Wellness. We will notice that all the experience of God provokes ecstasy that presents the Meaning, the fundament of the existence. And to educate is nothing more than to humanize by the Meaning, through Esthetic and the Playful via.